Student employment and work values across borders - Comparative study of students from two Carpathian Basin universities - Bocsi, Veronika; Jancsák, Csaba; Szőcs, Andor (Central European Journal of Educational Research, 2026)
This study examines the correlations between student employment and work values among full-time students at the University of Szeged (SZTE) in Hungary and Sapientia Hungarian University of Transylvania (Sapientia, Romania) in Romania. The research aims to explore whether the propensity for employment and attitudes toward work are primarily shaped by individual value orientations or by structural factors, such as family background and the institutional academic milieu. The empirical basis of the study is a database (N=2078) compiled from two questionnaire-based surveys conducted in 2024. The analysis employs descriptive statistics, factor analysis, and a binary logistic regression model. Findings indicate that the proportion of working students is significantly higher at Sapientia (56.5%) than at the University of Szeged (29.0%). Regarding work values, work-life balance and a positive workplace atmosphere are of paramount importance to students. Based on the regression model, the intention to work is positively influenced by higher paternal educational attainment, as well as by ’stability and work-oriented’ and ’socially responsible’ value orientations; conversely, gender and socio-economic status did not prove to be significant predictors. The study’s primary conclusion is that student employment today is no longer merely a consequence of financial necessity but a complex phenomenon determined by local factors and value systems. Our research highlights that the act of seeking employment is shaped by complex explanatory variables that should not be reduced solely to social background.